Trends in Body Mass Index and Associations With Physical Activity Among Career Soldiers in South Korea - Bae, Kyoung-Ki (The Korean Society for Preventive Medicine, 2011)
OBJECTIVE: This study was designed to describe the trends in body mass index (BMI) during 6 years (2002 - 2008) and to identify associations between these trends and the amount of physical activity of South Korean career soldiers. METHOD: This study targeted the 40 993 (38 857 men and 2136 women) of the 58 657 career soldiers who had undergone four (2002, 2004, 2006, and 2008) biennial medical examinations conducted by the National Health Insurance Corporation; 17 664 soldiers with missing data on height, weight, and physical activity were excluded. A linear mixed-regression model was used to categorize changes in BMI due to age versus those due to amount of physical activity. RESULTS: Career soldiers experienced significant increases in BMI compared with baseline data gathered in 2002. The increases in each age group were as follows: men aged 20- 29: 1.16, men aged 30 - 39: 0.61, men aged 40 - 49: 0.05, women aged 20- 29: 0.35, women aged 30- 39: 0.30, women aged 40-49: 0.26, and women aged 50- 59: 0.21. However, men aged 50 or older showed significant decreases (as high as 0.5) in BMI compared with baseline data obtained in 2002. They also experienced significant decreases in BMI compared with those who reported no physical activity. The differences between baseline and final BMIs were: 0.02 for men exercising 1- 2 times per week, -0.07 for men exercising 3-4 times per week, -0.19 for men exercising 5-6 times per week, -0.21 for men exercising seven times per week, -0.05 for women exercising 1- 2 times per week, -0.19 for women exercising 3- 4 times per week, -0.30 for women exercising 5-6 times per week, and -0.30 for women exercising seven times per week. CONCLUSIONS: Obesity in South Korean career soldiers increased markedly between 2002 and 2008, and our data showed that the amount of physical activity was inversely related to increases in BMI. Policies to prevent obesity are needed to reduce this trend.